Challenges in the management of acquired tracheal stenosis: a case report - Šuškevičienė, Ilona; Bukauskas, Tomas; Karbonskienė, Aurika; Macas, Andrius (Acta medica Lituanica, 2012)
Nowadays intubation is thought to be a safe, routine and life-saving pro cedure. Prolonged endotracheal intubation can result in fibrin deposits and predispose to the development of tracheal stenosis. The most com mon site for the occurrence of intubation-induced tracheal damage is at the area in contact with the inflatable cuff. We demonstrate the case re port that such injuries may lead to serious complications such as tracheal and laryngeal stenosis. The treatment is quite difficult and associated with significant risk and complications.
Keywords: tracheal stenosis; subglottic stenosis; tracheostomy; stridor; rigid bronchoscopy; high frequency jet ventilation